Focusing on the Medically Ready for Discharge Patient Using a Reliable Design Strategy: A Quality Improvement Project to Improve Length of Stay on a Medicine Service. Issue 1 (January 2022) - Meo, Nicholas; Cornia, Paul B.
Abstract : Background and Objectives: Length of stay is a common measure of efficiency of care. We aimed to reduce length of stay on a general medicine service through a structured quality improvement project. Methods: A reliable design strategy was implemented in successive stages at a 238-bed academically-affiliated VA hospital. Over a 2-year period, continuous improvement efforts were directed at discrete cohorts of patients deemed medically appropriate for discharge but who remained hospitalized because of discharge barriers. We compared the mean length of stay and medically-ready bed days of care for a hospital in statistical control charts. Pre- and post-intervention comparisons were made using t -tests. Results: In total, 5321 discharges were included in this improvement project, accounting for 35 852 bed days of care. Overall, average length of stay was reduced by 15.7%, from 7.62 to 6.40 days ( P < .05). There was a significant reduction in the mean number of medically-ready bed days of care from 2.3 to 1.72. Statistical process control charts demonstrated special cause variation across patient cohorts. Conclusion: A quality improvement project using reliable design principles was associated with shorter length of stay.